2015
DOI: 10.5010/jpb.2015.42.3.228
|View full text |Cite
|
Sign up to set email alerts
|

Effect of explant’s position and culture method on shoot proliferation and micro-cuttings for a rare and endangered species, Abeliophyllum distichum Nakai

Abstract: Using either the apical or axillary bud of the endangered species Abeliophyllum distichum Nakai, we tested the effect of bud position and culture method on shoot proliferation and rooting. In shoot proliferation, the axillary bud explant was more effective than the apical bud and the effect was fostered by BA treatment, whereas no differences were observed in shoot elongation by the explant position. Spontaneous rooting was observed in the MS basal medium and resulted in conspicuous differences in the explant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In addition, regeneration from embryogenic callus of old wild ginseng (Panax ginseng) via somatic embryogenesis has been reported (Bae and Choi, 2014). Lee et al (2015) (Kang et al, 2007), and also has been designated as an endangered species B2ab (ii, iii, v) on the International Union for Conservation of Nature (IUCN) Red List (IUCN, 2012). Despite the importance of this species, only a few studies related to its environmental characteristics (Cho et al, 2013), vegetation structure (Kang et al, 2007), and genetic diversity (Chung et al, 2013) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, regeneration from embryogenic callus of old wild ginseng (Panax ginseng) via somatic embryogenesis has been reported (Bae and Choi, 2014). Lee et al (2015) (Kang et al, 2007), and also has been designated as an endangered species B2ab (ii, iii, v) on the International Union for Conservation of Nature (IUCN) Red List (IUCN, 2012). Despite the importance of this species, only a few studies related to its environmental characteristics (Cho et al, 2013), vegetation structure (Kang et al, 2007), and genetic diversity (Chung et al, 2013) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high scarcity and ecological and geographic value, A. distichum has rarely been studied compared with other plants. However, in 2017, A. distichum was removed from the list of endangered species by the Ministry of the Environment [ 6 ] due to the development of mass breeding techniques [ 7 , 8 ]. Previous phytochemical studies of these plants have focused on just the leaves, and they reported that four phenylethanoid glycosides and two flavonoids are components of these plants [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%